The Boer goats. II. Growth, nutrient requirements, carcass and meat quality - Niekerk, W.A. van; Casey, N.H. (Elsevier, 1988)
Growth rates of Boer goats were generally lower than sheep and, under favorable nutritional conditions, weight gains of more than 200 g per day were obtained, against values of up to 176 g per day under extensive subtropical conditions. Lactation and pregnancy had a marked effect on ME intake, and the latter had an improved feed conversion ratio (6.06 kg/kg) in comparison to that of virgin does (10.96 kg/kg). Below 6% crude protein in the diet, feed intake is reduced and has negative effects on birth weights, growth and milk production. Little information is available on mineral requirements of goats. The carcass of Boer goats is generally leaner, less compact and has different carcass proportions than sheep. The relatively high collagen contents with lower solubility of Boer goat meat, has meant that the eating quality has been regarded as inferior to that of Iamb and mutton. Breeding holds the key to improving tenderness of goat meat; different slaughtering techniques can be used as well. Boer goats have high potential as meat animals when yielding three kid crops in 2 years and when fed to gain more than 200 g/day.